(untitled) (UNED Research Journal, 2016)
Costa Rica is a country with a high biological diversity that protects one quarter of its territory and has the highest educational level in Central America. We expected Costa Ricans to be familiar with their mammals. To test our hypothesis, we asked a sample of citizens of San Ramon, Costa Rica, to identify photographs of mammals, both native and exotic. Against our hypothesis, they identified less native than exotic species. Men recognized more native species than women, and the youngest persons more exotic species. Education and rural or urban origin made no difference. Mass media play a key role in the transmission of knowledge about biodiversity; this explains why exotic species (which have greater coverage in the media) are better known than some local species.